Utility of left atrial and ventricular strain for diagnosis of transthyretin amyloid cardiomyopathy in aortic stenosis - Fumi Oike; Hiroki Usuku; Eiichiro Yamamoto; Kyohei Marume; Seiji Takashio; Masanobu Ishii; Noriaki Tabata; Koichiro Fujisue; Kenshi Yamanaga; Daisuke Sueta; Shinsuke Hanatani; Yuichiro Arima; et al. (ESC Heart Failure)
Abstract Aims To clarify the usefulness of left atrial (LA) function and left ventricular (LV) function obtained by two‐dimensional (2D) speckle tracking echocardiography to diagnose concomitant transthyretin amyloid cardiomyopathy (ATTR‐CM) in patients with aortic stenosis (AS). Methods and results We analysed 72 consecutive patients with moderate to severe AS who underwent 99mTc‐pyrophosphate (PYP) scintigraphy at Kumamoto University Hospital from January 2012 to September 2020. We divided these 72 patients into 2 groups based on their 99mTc‐PYP scintigraphy positivity or negativity. Among 72 patients, 16 patients (22%) were positive, and 56 patients (78%) were negative for 99mTc‐PYP scintigraphy. In clinical baseline characteristics, natural logarithm troponin T was significantly higher in the 99mTc‐PYP scintigraphy‐positive than scintigraphy‐negative group (−2.9 ± 0.5 vs. −3.5 ± 0.8 ng/mL, P < 0.05). In conventional echocardiography, the severity of AS was not significantly different between these two groups. In 2D speckle tracking echocardiography, the relative apical longitudinal strain (LS) index (RapLSI) [apical LS/ (basal LS + mid LS)] was significantly higher (1.09 ± 0.49 vs. 0.78 ± 0.23, P < 0.05) and the peak longitudinal strain rate (LSR) in LA was significantly lower in the 99mTc‐PYP scintigraphy‐positive than scintigraphy‐negative group (0.36 ± 0.14 vs. 0.55 ± 0.20 s−1, P < 0.05). Multivariable logistic analysis revealed the peak LSR in LA and RapLSI were significantly associated with 99mTc‐PYP scintigraphy positivity. Receiver operating characteristic analysis showed that the area under the curve (AUC) of the peak LSR in LA for 99mTc‐PYP scintigraphy positivity was 0.79 and that the best cut‐off value of the peak LSR in LA was 0.47 s−1 (sensitivity: 78.6% and specificity: 72.3%). The AUC of RapLSI for 99mTc‐PYP scintigraphy positivity was 0.69, and the cut‐off value of RapLSI was decided as 1.00 (sensitivity: 43.8% and specificity: 87.5%) according to the previous report. The 99mTc‐PYP scintigraphy positivity in patients with RapLSI ≥ 1.0 and the peak LSR in LA ≤ 0.47 s−1 was 83.3% (5/6), and the 99mTc‐PYP scintigraphy negativity in patients with RapLSI < 1.0 and the peak LSR in LA > 0.47 s−1 was 96.6% (28/29). Conclusions Left atrial and LV strain analysis were significantly associated with 99mTc‐PYP scintigraphy positivity in ATTR‐CM patients with moderate to severe AS. The combination of the peak LSR in LA and RapLSI might be a useful predictor of the presence of ATTR‐CM in patients with moderate to severe AS.